Lightning protection of overhead power transmission lines with composite towers - Balyuk, Oleksandr (National Technical University "Kharkiv Polytechnic Institute", 2024)
The features of lightning protection of overhead power transmission lines are considered, and the key aspects of technical improvement and advantages of using composite materials in this area are identified. The current state of the problem, technical properties and advantages of using composite poles in electrical grids, as well as possible challenges and prospects for improving lightning protection using these technologies are analysed. The results of the investigation can be useful for the energy industry and researchers in the field of power transmission, as well as for developers of technologies in the field of lightning protection and composite materials.
Keywords: lightning protection; composite towers; transmission lines; lightning current; surges voltage; technical improvement; stability; reliability; energy efficiency